Penerapan Media Pembelajaran Interaktif Berbasis Educaplay Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas IX SMPmp Negeri 02 Sumber Pada Materi Reaksi-Reaksi Kimia Dan Dinamikanya - Putri Marfhadella; Nurwanti Fatnah; Adiyanti (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to improve science learning outcomes in the sub-material of chemical reactions and their dynamics by implementing Educaplay-based learning media. The method used in this research is Classroom Action Research (CAR), which was carried out in two cycles. Each cycle includes four stages: planning, implementation, observation, and reflection. The research subjects were 31 ninth-grade students of class IX G at SMP Negeri 02 Sumber, Cirebon Regency, West Java Province. The selection of research subjects was based on observations and students' previous learning outcomes in science subjects. Through the two research cycles, a consistent improvement in learning outcomes was observed. The pre-test results showed 12.9%, which increased to 41.93% in the post-test of the first cycle, and further rose to 81% in the post-test of the second cycle. This means that students who scored ≥ 80 had met the learning outcome indicator of 80%. Thus, the difference in learning outcomes from the first to the second cycle was 39%, indicating a significant improvement in student performance. Based on the observation results in the first cycle, the teacher's activity score reached 70%, categorized as good, and increased to 92% in the second cycle, categorized as very good—an improvement of 22%. Meanwhile, student activity in the first cycle was 68%, categorized as fair, and increased to 90% in the second cycle, categorized as very good, also showing a 22% improvement.